What are we to make of safe behaviour programs? - Hopkins, Andrew (Camberra, 2006)
"Safe behaviour programs are currently a popular strategy for improving safety in large organizations. This paper provides a critical look at the assumptions which underly such programs and identifies some of their limitations. Safe behaviour programs run the risk of assuming that unsafe behaviour is the only cause of accidents worth focusing on. The reality is that unsafe behaviour is merely the last link in a causal chain and not necessarily the most effective link to focus on, for the purposes of accident prevention. One major drawback of these programs is that they miss critically important unsafe behaviour, such as attempts by workers to re-start processes that have been temporarily interrupted. Conventional safe behaviour programs aimed at front line workers are also of no use in preventing accidents in which the behaviour of front line workers is not involved. Given that it is the behaviour of management which is most critical in creating a culture of safety in any organization, behavioural safety observations are likely to have their greatest impact if directed upwards, at managers. The paper concludes with an appendix about accident repeater programs which are sometimes introduced along with safe behaviour programs."